John Buridan's Quaestiones de secretis mulierum: Edition and Introduction. - Beneduce, Chiara; Bakker, Paul J.J.M. (Vivarium, 2019)
This article provides the first edition of a series of eight Quaestiones de secretis mulierum by (or ascribed to) John Buridan († ca. 1360). The introduction discusses the manuscript tradition and the relationship between Buridan's quaestiones and pseudo-Albertus Magnus' treatise De secretis mulierum , concluding that Buridan's questions constitute a genuine commentary on pseudo-Albert's text. Specifically, the eight questions by (or ascribed to) Buridan seem to be an extensive elaboration on the preface (prologus) and on the first chapter of pseudo-Albert's text.